Evaluation of E-Learning in teaching Practical Oral Pathology during Covid-19 pandemic - يوسف , باسمة (Latakia University Journal -Medical Sciences Series, 2021)
E-Learning has been used in healthcare education Programmes in many universities during Covid 19 Pandemic. The purpose of this study was to evaluate the E-Learning in teaching practical oral Pathology in the Histology and Pathology Department in Dental faculty in Tishreen University Methods: I compare the result of the final practical Test of the (100) students included the test of two methods . using T-test for statistical analysis and the result were considered significant in case of P< 0,05. Results: The mean score of the result of the Test of e-Learning methods was higher the the result of traditional test and the difference was statistically significant . Conclusions: E-learning method was the best in teaching practical oral pathology and more researches must be done about other subjects and improve the guality of E-Learning .